2019
DOI: 10.1002/marc.201900310
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Heterodifunctional Unimolecular Ring‐Closure Method for Cyclic Polymers by Combining RAFT and SuFEx Click Reactions

Abstract: A novel ring‐closure strategy for cyclic polymers by combining reversible addition–fragmentation chain transfer polymerization (RAFT) and the sulfur(VI)‐fluoride exchange (SuFEx) click reaction is presented. Herein, a new heterodifunctional trithiocarbonate RAFT agent, 2‐((tert‐butyldimethylsilyl)oxy)ethyl (4‐(fluorosulfonyl)benzyl) carbonotrithioate (TBDMS‐FSBCT), containing both tert‐butyldimethylsilyl ether and sulfonyl fluoride moieties, is developed. The polymerization behavior of TBDMS‐FSBCT is first dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…In the framework of Sulfur( vi )–Fluoride Exchange (SuFEx) chemistry—an umbrella term for substitution events replacing fluoride at the electrophilic sulfur center—these ‘ molecular plugins ’ allow selective and efficient installation of linkages around the S VI core. Especially in the last seven years, various research groups have demonstrated the potential of SuFEx hubs such as sulfonyl fluorides (R–SO 2 F), 1 sulfuryl fluoride (SO 2 F 2 ), 2 thionyl tetrafluoride (SOF 4 ), 3 ethenesulfonyl fluoride (ESF, CH 2 CH–SO 2 F), 2 a ,4 and others. 5 The chemoselective and straightforward nature of SuFEx chemistry has enabled a range of applications in synthesis and materials.…”
Section: Introductionmentioning
confidence: 99%
“…In the framework of Sulfur( vi )–Fluoride Exchange (SuFEx) chemistry—an umbrella term for substitution events replacing fluoride at the electrophilic sulfur center—these ‘ molecular plugins ’ allow selective and efficient installation of linkages around the S VI core. Especially in the last seven years, various research groups have demonstrated the potential of SuFEx hubs such as sulfonyl fluorides (R–SO 2 F), 1 sulfuryl fluoride (SO 2 F 2 ), 2 thionyl tetrafluoride (SOF 4 ), 3 ethenesulfonyl fluoride (ESF, CH 2 CH–SO 2 F), 2 a ,4 and others. 5 The chemoselective and straightforward nature of SuFEx chemistry has enabled a range of applications in synthesis and materials.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Among these polymerization techniques, the RAFT process is particularly suitable for the preparation of terminal functional polymers due to its compatibility with a broader range of monomers and reaction media. For example, terminal functional polymers with linear, 11 star, 12 brush, 13 ring, 14 and other molecular architectures have been synthesized through the design of RAFT reagent structures. 2,3 Since the concept of click chemistry was first proposed by Sharpless et al in 2001, 15 it has been widely developed due to its characteristics of high efficiency and robust, rapid, and specific reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The TBS and fluorosulfonyl end groups were stable during RAFT polymerization of Nisopropylacrylamide (NIPAAm) and N-vinylpyrrolidone (NVP), and intramolecular SuFEx cyclization performed under ambient condition in high yield. 352…”
Section: Single Cyclic Polymersmentioning
confidence: 99%